2000
DOI: 10.2337/diacare.23.12.1770
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of fasting plasma glucose and HbA1c predicts the progression to diabetes in Chinese subjects.

Abstract: OBJECTIVE -We have previously suggested using the paired values of fasting plasma glucose (FPG) and HbA 1c to identify potential diabetic subjects. In this article, we followed up on 208 nondiabetic subjects and examined their rates of progression to diabetes. We analyzed their likelihood of becoming diabetic according to their baseline FPG and HbA 1c concentrations. -Between 1988 and 1995, 2,877 Chinese subjects with risk factors for diabetes underwent screening. Of these, 2,250 had FPG Ͻ7.8 mmol/l and 2-h p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
45
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 18 publications
8
45
0
Order By: Relevance
“…A study in Pima Indians (15) reported that A1C was an independent predictor for diabetes only in individuals with IGT, not in subjects with normal 2-h plasma glucose. The same relation was found in a Chinese study (16).To determine whether A1C predicted incident diabetes after a 6-year follow-up in a Caucasian population, we analyzed data from the prospective French cohort study: Data from an Epidemiological Study on the Insulin Resistance Syndrome (DESIR).RESEARCH DESIGN AND METHODS -The 3,854 subjects studied, aged 30 -65 years, were included in 1994 -1996 in the DESIR Study, a follow-up study on the development of the insulin resistance syndrome. They were volunteers for a routine health check-up in seven Health Examination Centers financed by the French Social Security in the center-west of France.…”
supporting
confidence: 74%
“…A study in Pima Indians (15) reported that A1C was an independent predictor for diabetes only in individuals with IGT, not in subjects with normal 2-h plasma glucose. The same relation was found in a Chinese study (16).To determine whether A1C predicted incident diabetes after a 6-year follow-up in a Caucasian population, we analyzed data from the prospective French cohort study: Data from an Epidemiological Study on the Insulin Resistance Syndrome (DESIR).RESEARCH DESIGN AND METHODS -The 3,854 subjects studied, aged 30 -65 years, were included in 1994 -1996 in the DESIR Study, a follow-up study on the development of the insulin resistance syndrome. They were volunteers for a routine health check-up in seven Health Examination Centers financed by the French Social Security in the center-west of France.…”
supporting
confidence: 74%
“…Previous studies have shown that circulating HbA1c levels are associated with the conversion of pre-diabetic phase into clinical diabetes [35][36][37][38]. Further, a strong association between baseline HbA1c and incidence of type 2 diabetes was also suggested in a large-scale prospective study among middle aged women [39].…”
Section: Discussionmentioning
confidence: 66%
“…Many studies in western literature, have advocated the use of HbA1c for diagnosis of diabetes (5,6,7). When both FPG and A1C were measured, a stronger correlation was found between A1C and retinopathy than between fasting glucose levels and retinopathy (7) Studies that have assessed glycemia with A1C or with single or longitudinal measurements of glucose levels have consistently demonstrated a strong correlation between retinopathy and In our country, patient compliance is a major problem.…”
Section: Discussionmentioning
confidence: 99%